Association Between the Diabetic Foot Ulcer and the Bacterial Colony of the Skin Based on 16S rRNA Gene Sequencing: An Observational Study - Zhang XN; Wu CY; Wu ZW; Xu LX; Jiang FT; Chen HW (Dove Medical Press, 2023)
Xiu-Ni Zhang,1 Cui-Yi Wu,2 Zhi-Wei Wu,1 Li-Xian Xu,3 Feng-Ting Jiang,1 Han-Wei Chen4 1Department of Trauma Orthopedics, Panyu Central Hospital, Guangzhou, Guangdong, 511400, People's Republic of China; 2Department of Outpatient, Panyu Central Hospital, Guangzhou, Guangdong, 511400, People's Republic of China; 3Department of Endocrinology, Panyu Central Hospital, Guangzhou, Guangdong, 511400, People's Republic of China; 4Administrative Office, Panyu District Health Management Center, Guangzhou, Guangdong, 511400, People's Republic of ChinaCorrespondence: Xiu-Ni Zhang, Email zxn18926220698@163.comObjective: Microorganisms have been the main cause of refractory and high recurrence of diabetic foot ulcer (DFU). This study attempted to observe the skin bacterial colony in healthy skin, diabetic skin and DFU skin.Methods: Forty-eight diabetes patients were recruited at Panyu Central Hospital from March 2021 to March 2022 and divided into DFU group (T group, n = 22), diabetes without foot ulcer group (TW group, n = 26). Besides, a healthy control group (H group, n = 10) was recruited at the same time. The swab samples of foot skin in the same position in the three groups were collected. The microorganisms obtained from the skin were analyzed by 16S rRNA gene sequencing. The composition of the skin microorganisms was determined, and the species diversity of the skin microbiota was analyzed by α and β diversity. The species differences in the skin microbiota and the relative abundance of different operational taxonomic units (OUTs) with the most significant abundance were analyzed by linear discriminant analysis effect size (LEfSe).Results: Significant changes were found in the composition of the skin microbiota in the T and TW groups relative to the H group. However, the species diversity of the skin microbiota was significantly reduced in the T and TW groups, with the lowest one in the T group. The composition of microbial diversity in the T group was significantly different from that of the TW and H groups. Among the skin bacterial colonies, the abundance of Staphylococcus, Enhydrobacter, and Corynebacterium_1 was obviously reduced, while that of Escherichia coli and Pseudomonas was significantly increased.Conclusion: Changes in the abundance of Staphylococcus, Enhydrobacter, Corynebacterium_1, Escherichia coli and Pseudomonas in the skin bacterial colonies can be the main causative factors for DFU. This study indicates that altering the microbiota composition of wounds may help the treatment of DFU.Keywords: diabetes, foot ulcers, skin bacterial colony, 16S rRNA gene sequencing